2019
DOI: 10.1111/1440-1703.12052
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil bacterial compositions to concentrations of nitrogen forms in the process of Moso bamboo invasion

Abstract: We analyzed and compared the soil bacterial diversity and difference in community composition in a Moso bamboo forest, a mixed Moso bamboo–conifer (Pinus massoniana) forest, and a coniferous forest. The relative abundances of Acidobacteria and Planctomycetes were significantly lower in the Moso bamboo forest, while those of Actinobacteria, Bacteroidetes, TM‐7 and Chlamydiae were greatly increased. The α‐diversity in the Moso bamboo forest was different from that in the other two forest types but was not statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
1
1
Order By: Relevance
“…In our experiment, ammonia N decreased, and nitrate N increased, which was similar to the research results of short-term N input by Hall and Matson [46], indicating that the net nitrification rate gradually increased with increasing N addition dose [47]. In general, the moso bamboo forest was short of N, especially with respect to the natural growth status, i.e., 20 years in our study, which is related to its preference for ammonium-N and strong clonal breeding habits [48]. Therefore, N deposition in moso bamboo forests can alleviate the degradation of ecosystems caused by N deficiency to a certain extent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our experiment, ammonia N decreased, and nitrate N increased, which was similar to the research results of short-term N input by Hall and Matson [46], indicating that the net nitrification rate gradually increased with increasing N addition dose [47]. In general, the moso bamboo forest was short of N, especially with respect to the natural growth status, i.e., 20 years in our study, which is related to its preference for ammonium-N and strong clonal breeding habits [48]. Therefore, N deposition in moso bamboo forests can alleviate the degradation of ecosystems caused by N deficiency to a certain extent.…”
Section: Discussionsupporting
confidence: 89%
“…After SND, F:B decreased due to the decline in C:N, mainly because K-strategy fungi had higher biomass C:N than bacteria [3]. Li et al [48] suggested that N deposition can increase the soil MBC content, thus increasing MBC:MBN and reducing competition between plants and microorganisms [58]. Our results showed some differences from those conclusions, as they indicated that MBC decreased while MBC:MBN changed little.…”
Section: Discussioncontrasting
confidence: 80%
“…Bamboo is regarded as an invasive species because of its strong reproductive ability, rapid growth rate, and intertwined underground rhizome roots, which intertwine with each other. Following the introduction of bamboo, the soil ecology of mixed forests can easily change, including soil pH, biodiversity, enzyme activity, and nutrient composition [30][31][32][33][34][35]. Bamboo is not a halophyte; however, there are reports of its planting on saline-alkali land, and it is believed that bamboo plants have some saline-alkali tolerance.…”
Section: Introductionmentioning
confidence: 99%